Problem Solving Skills Analysis of Vocational Engineering Teacher Candidates in Term of Several Variables - Anwar, Muhammad (Journal of Education Technology, 2021)
Higher order thinking skills, especially problem-solving skills, are very important for prospective vocational teachers. Not only to be transmitted to their students, but also necessary for teachers to carry out 21st century learning. Unfortunately, teaching problem solving skills to the teacher candidates is not conducted in the classroom yet. This study aims to measure the problem-solving skills of vocational teacher candidates at the Faculty of Engineering of UNP. This research was conducted using a descriptive type general survey method. By using the Slovin formula and a 5% error, a sample of 340 students was selected in a proportionate stratified from 2289 FT UNP (Vocational Engineering Study Program) students as the population. The data were collected using a problem-solving skills questionnaire that was rearranged based on Basadur's concept of the simplexity thinking. However, this study shows that there is a significant difference (p <0.05) of problem-solving skills based on the level of satisfaction of teacher candidates with the learning methods implemented by the lecturers. However, there were no significant differences in problem-solving skills based on study program, gender, high school background, and entrance year (p> 0.05) after being analyzed by one-way ANOVA. This study shows that satisfaction of learning process is in line with the problem-solving skills of prospective teachers. For this reason, it is very important for vocational teacher education institutions to teach problem-solving skills and maintain high level of students’ satisfaction in the learning process.